Go big : lead your church to explosive growth - Easum, William M., 1939- (Abingdon Press, 2006)
Bill Easum and Bil Cornelius are two strikingly different, yet surprisingly similar pastors. One undertook to revitalize a moribund mainline church; the other, to plant a new nondenominational congregation. Coming from different generations, their ministries took place under dissimilar circumstances. Yet both have experienced substantial, even explosive, growth in congregational mission and membership. Along the way they learned some important lessons, such as the centrality of strong pastoral leadership, the need for an unhesitant pursuit of excellence in all areas of the church's ministry, a.